Document forensic, the fiqh and the Syariah Courts - Wan Abdul Fattah Wan Ismail,; Lukman Abdul Mutalib,; Zul Hilmi Abdullah,; Abd Hamid Abd Murad,; Nurfadhilah Che Amani,; Madihah Mohammad Khir, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Technological progress has made falsification of documents increasingly sophisticated and the need for forensic experts or Ra'yu al-Khabir indispensable in the Syariah Courts. This paper discusses the concept and methods of forensic document authentication by experts according to the Islamic law (fiqh). This study combined quantitative and qualitative approaches whereby 181 key informants comprising randomly sampled syariah and civil law experts and practitioners underwent in-depth interviews . Content analysis of the study revealed that respondent knowledge of document authentication methods according to the Islamic law was at the intermediate level with the mean = 3.59 and sd = 0.63 which was not enough to help the Syariah Courts cope with the rapid increase in the falsification rate of documents. This situation needs urgent redress and calls for the establishment of a comprehensive forensic model to provide adequate guidelines for judges and practitioners of the Syariah Courts.